2010
DOI: 10.1111/j.1467-8535.2009.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessor or assessee: How student learning improves by giving and receiving peer feedback

Abstract: This study investigated the relationship between the quality of peer assessment and the quality of student projects in a technology application course for teacher education students. Forty-three undergraduate student participants completed the assigned projects. During the peer assessment process, students first anonymously rated and commented on two randomly assigned peers' projects, and they were then asked to improve their projects based on the feedback they received. Two independent raters blindly evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
184
2
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(228 citation statements)
references
References 13 publications
12
184
2
12
Order By: Relevance
“…The above results are inline with previous studies that report beneficial learning outcomes (a) when students get multiple reviews (as opposed to getting a single review) (Cho & Schunn, 2007), and (b) when students act as "givers" (that is when they provide reviews) compared to acting as "receivers" (getting peer feedback) (Lundstrom & Baker, 2009;Li, Liu & Steckelberg, 2010;Reily, Finnerty & Terveen, 2009). Furthermore, the students' positive approach to the FS method is also in line with other studies reporting tendency of students to contribute more when not restricted by the assignment protocol (Luxton-Reilly, 2009).…”
Section: Revision Process: Are the Revised Answers Equally Good?supporting
confidence: 79%
See 1 more Smart Citation
“…The above results are inline with previous studies that report beneficial learning outcomes (a) when students get multiple reviews (as opposed to getting a single review) (Cho & Schunn, 2007), and (b) when students act as "givers" (that is when they provide reviews) compared to acting as "receivers" (getting peer feedback) (Lundstrom & Baker, 2009;Li, Liu & Steckelberg, 2010;Reily, Finnerty & Terveen, 2009). Furthermore, the students' positive approach to the FS method is also in line with other studies reporting tendency of students to contribute more when not restricted by the assignment protocol (Luxton-Reilly, 2009).…”
Section: Revision Process: Are the Revised Answers Equally Good?supporting
confidence: 79%
“…(1) The literature suggests that in order for students to successfully carry out an assessment of their peers they need to be prepared for the assessment (Loddington et al, 2008) (2) The quality of peer feedback can affect its impact (Gielen et al, 2010) (3) The "givers", who focused solely on reviewing peers' writing, made more significant gains in their own writing over the course of the semester than did the "receivers", who focused solely on how to use peer feedback (Lundstrom & Baker, 2009;Li, Liu & Steckelberg, 2010;Reily, Finnerty & Terveen, 2009) Research Evidence Students receiving feedback from multiple peers improve their writing quality more than students receiving feedback from a single expert (Cho & Schunn, 2007) Against the above background, this study focuses on Phase 2 (assigning reviewers) and explores the potential of the Free Selection assignment protocol to improve learning outcomes (that is, allowing students to browse and select for themselves peer work for review). There is already in the literature indication that the "randomly assigned pair" protocol, implemented typically by the instructors, might not be the optimal selection regarding student learning.…”
Section: Key Research Questionsmentioning
confidence: 99%
“…One of the areas warranting further investigation with entering first-year college students is how varied their editorial comments are during peer editing tasks. A number of researchers have compared student and instructor comments on matching writing drafts and found many similarities (Gielen et al, 2010;Stellmack et al, 2012;Underwood & Tregidgo, 2005), particularly when steps are taken to increase understanding of assignment and grading requirements and the seriousness of the peer editing processes and when sufficient feedback is received (Cho & MacArther, 2011;Covill, 2010;Kaufman & Schunn, 2011;Li et al, 2009;McGroarty & Zhu, 1997). Given the variety of writing feedback, by type and amount, on the drafts collected in this study and by other researchers examining peer editing, issues of importance would seem to be quality of peer feedback (e.g., clarity of student writing suggestions, correction accuracy), and quality of the models provided by novice writers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that students did not learn much from providing low quality comments (Li et al, 2010). Students can also have anxiety about giving feedback (Ertmer, et al, 2007) if they are not used to this activity, as they do not want to appear to be criticizing peers' work.…”
Section: Rationale For Adopting Peer Feedbackmentioning
confidence: 99%
“…This process involves learners in thinking about quality, standards, and criteria that they may use to evaluate others' work, which helps them become critical thinkers and reflective learners (Liu & Carless, 2006). Li, Liu, and Steckelberg (2010) investigated the impact of peer assessment in an undergraduate technology application course. They found a positive and significant relationship between the quality of peer feedback that students provided for others and the quality of the students' own final products, controlling for the quality of the initial projects.…”
Section: Rationale For Adopting Peer Feedbackmentioning
confidence: 99%